2016
DOI: 10.1590/s0102-865020160020000004
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound biomicroscopy and claudication test for in vivo follow-up of muscle repair enhancement based on platelet-rich plasma therapy in a rat model of gastrocnemius laceration

Abstract: PURPOSE:To track the regeneration process of lateral gastrocnemius due to a muscle laceration in rats, and to treatment with plateletrich plasma (PRP). METHODS:Ultrasound (40 MHz) images were used for measuring pennation angle (PA), muscle thickness (MT) and mean pixel intensity, along with claudication scores, of treated (PRPG) and non-treated (NTG) groups of rats.RESULTS: NTG showed a PA increase for the non-injured leg (p<0.05) and a tendency of MT to increase, whereas for PRPG there were no differences. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Of the 2 studies that examined both the in vivo and in vitro uses of PRP, one used human muscle-derived progenitor cells (hMDPCs) from unspecified skeletal muscle from living and post-mortem biopsies for the in vitro component[26], while the other used an established murine myogenic cell line (C2C12)[27] (Table 6). Only one study reported platelet count and WBC concentration[24], while neither reported RBC count. For the in vivo component, the gastrocnemius muscle of a mouse[26] and the rotator cuff muscles (supraspinatus and infraspinatus) of a rat[27] were used.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 2 studies that examined both the in vivo and in vitro uses of PRP, one used human muscle-derived progenitor cells (hMDPCs) from unspecified skeletal muscle from living and post-mortem biopsies for the in vitro component[26], while the other used an established murine myogenic cell line (C2C12)[27] (Table 6). Only one study reported platelet count and WBC concentration[24], while neither reported RBC count. For the in vivo component, the gastrocnemius muscle of a mouse[26] and the rotator cuff muscles (supraspinatus and infraspinatus) of a rat[27] were used.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the limitations in human trials, with respect to PRP, there have been numerous progressions in the field of skeletal muscle regeneration in rodent models . Accumulating data from animal studies on the role of PRP on skeletal muscle recovery after varying types of injury has emerged (Table ).…”
Section: Platelet‐mediated Skeletal Muscle Regenerationmentioning
confidence: 99%
“…These factors in turn upregulate proliferation, differentiation and migration of necessary cells in the area of regenerating tissue . Over the past decade, there have been amounting articles contributing to the knowledge surrounding the mechanisms of growth factors in the regeneration of wounded or dysfunctional tissue . Due to increasing understanding in cell signalling and growth factor biology, research and clinical attention has been drawn to the use of autologous PRP as a novel means of delivering growth factors to injured tissue such as liver, bone and skeletal muscle (See Table : muscle tissue regeneration , Table : other tissue regeneration and Table : in vitro cell studies).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the reduction of type-I collagen deposition and scar formation (fibrosis) [106,110,112,113,115,116,117,118] the enhancement of angiogenesis [106,110,112,116,117] and a faster functional recovery [108,109,113,118,119] have been also observed after PRP application on damaged muscles. Takase and co-workers [120] recently demonstrated also the ability of PRP to prevent fatty degenerative changes of rotator cuff muscles in a rat rotator cuff tear model, when administered into subacromial space.…”
Section: Plasma Preparations: Platelet-rich Plasma (Prp) and Platementioning
confidence: 99%